Prevalence of oral trauma in Para‐Pan American Games athletes. Issue 4 (8th August 2012) - Andrade, Rafaela Amarante; Modesto, Adriana; Evans, Patricia Louise Scabell; Almeida, Anne Louise Scabell; de Jesus Rodrigues da Silva, Juliana; Guedes, Aurelino Machado Lima; Guedes, Fábio Ribeiro; Ranalli, Dennis N.; Tinoco, Eduardo Muniz Barretto
Abstract: The aim of this cross‐sectional epidemiological survey was to assess the prevalence of oral trauma in athletes representing 25 countries competing at the most recent Para‐Pan American Games (III PARAPAN) held in Rio de Janeiro, Brazil. The study was approved by the appropriate institutional review board. The examiners participated in standardization and calibration training sessions before the field phase began. Invitations were sent to >1200 participating athletes competing in eight sports and to the Medical Committee of the Para‐Pan American Sports Organization before and during the III PARAPAN. A convenience sample of 120 athletes was recruited. After signing an informed consent, all athletes answered a questionnaire. Data were collected at the clinical examination and recorded in a specific trauma form. The mean age of the athletes was 32.5 years. Males comprised 79.2% of the sample; females 20.8%. The prevalence of oral trauma among the athletes was 47.5% ( N  = 57). However, only 15 athletes reported that these traumatic injuries were sports‐related. The sport with the highest prevalence of oral trauma was judo (75%); the least was volleyball with no reported traumatic injuries. The most common traumatic injury was enamel fracture (27.4%). The teeth most affected were the maxillary permanent central incisors ( N  = 19), followed by the maxillary premolars ( N  = 8). On the basis of the results of this study of oral trauma among athletes examined at the III PARAPAN, a recommendation for enhanced educational efforts and the use of properly fitted mouthguards to prevent traumatic injuries among high‐performance athletes with disabilities seems warranted.